WORK WITHOUT PROTECTIONS: THE SOCIAL DIMENSIONS OF EXPLOITATION AND PRODUCTIVITY IN NIGERIA’S INFORMAL ECONOMY - Chinyelu Udeobasi, Obianuju; Valentine Ekechukwu, Iheanyi; Onyebuchi Oguamanam, Gabriel; Chiedozie Udeji, Nixon; Odinaka Ugwukwu, Vitalis (African Journal of Social and Behavioural Sciences, 2026)
Nigeria’s informal sector plays a vital role in sustaining livelihoods, providing employment for a large share of the population and contributing significantly to everyday economic survival. Yet, behind this importance lies a reality shaped by insecurity, weak protections, and difficult working conditions. Many informal workers operate without stable contracts, social security, or safe work environments, and these challenges often limit how productive they can be. This study adopts a qualitative documentary research design, relying on secondary data drawn from scholarly literature, policy documents, and institutional reports to examine how labour insecurity influences productivity in Nigeria’s informal economy. Using Marxist Labour Theory as a guiding lens, it explains that issues such as low wages, job insecurity, lack of social protection, and unsafe workplaces are not random problems but part of a broader system that places workers in vulnerable positions. As a result, many workers struggle not because they are unwilling or unskilled, but because the conditions of their work reduce their capacity to perform effectively. The paper argues that improving productivity in the informal sector requires more than short-term or technical solutions. It calls for deeper reforms that prioritize fairness, protection, and inclusion in labour relations. In particular, it recommends expanding social protection coverage to informal workers through schemes such as the National Health Insurance Authority (NHIA), alongside simpler pathways for gradual formalization. Ultimately, the study highlights the need to recognize informal workers as essential contributors to Nigeria’s economy who deserve dignity, protection, and support.